Melting heat transfer in an axisymmetric stagnation-point flow of the Jeffrey fluid - Nawaz, M.; Hayat, T.; Zeeshan, A. (Journal of applied mechanics and technical physics, 2016)
This investigation explores the characteristics of melting heat transfer in a boundary layer flow of the Jeffrey fluid near the stagnation point on a stretching sheet subject to an applied magnetic field. The governing boundary layer equations are transformed to ordinary differential equations by similarity transformations. Resulting nonlinear problems are solved analytically by the homotopy analysis method. It is noticed that an increase in the melting parameter decreases the dimensionless velocity and temperature, while an increase in the Deborah number increases the velocity and momentum boundary layer thickness.